Physical activity and lifestyle of older adults in the context of diseases of affluence - Alena Buková; Agata Horbacz; Ladislav Kručanica; Mária Majherová (Lesya Ukrainka Volyn National University, 2019)
Introduction. In this study, we focused on physical activity of older adults and their lifestyle in the context of diseases of affluence. We monitored the most common physical activity performed by older adults, weekly frequency of the chosen physical activity, together with the prevalence of diseases of affluence and the assessment of the life quality of older adults. Methods. The study group comprised active older adults (n=35) who performed regular physical activity two and more times weekly, with two times a week under the supervision of an experienced instructor, and inactive older adults (n=35) whose physical activities consisted of only short walks and irregular exercise. Results. We found a lower prevalence of diseases of affluence among active older adults compared to the inactive. The differences are significant, especially in peripheral vascular disorders, osteoporosis, and diabetes. However, a statistically significant difference was only found in problems with blood pressure. Half of the inactive older adults reported that the diseases had restricted their physical activity, but they did not feel the need for any additional physical exercise. As we assumed, a significantly higher number of active older adults was recorded in the group with higher life quality. Conclusion. We agree with opinions of professionals in the field who recommend PA to be a natural and everyday part of a daily routine not only in younger age groups but also in retirement. There is a higher prevalence of chronic diseases in older adults, and therefore, they should understand the importance and meaning of PA in alleviating the irreversible process of aging.